Differential transport pathways of saturated and unsaturated fatty acid esters in male mouse hepatocytes - Fengwu Chen; Aizhen Yang; Yue Lu; Yuxin Zhang; Jingyu Zhang; Jianan Bu; Runlin Guo; Yue Han; Depei Wu; Yi Wu (Nature Communications)
Abstract Saturated fatty acid (SFA) and unsaturated fatty acid (UFA) have distinct impacts on health. Whether SFA and UFA are differentially transported in liver remains elusive. Here, we find the secretion of UFA but not SFA esters is retarded in a male mouse hepatic endoplasmic reticulum (ER) stress model. Among 13 members of protein disulfide isomerase (PDI) family, only PDIA1 (PDI) deficiency leads to hepatosteatosis and hypolipidemia. In PDI-deficient male mouse liver, there is a severe accumulation but secretory blockade of UFA esters, whereas the accumulation and secretion of SFA esters remain normal. PDI catalyzes the oxidative folding of microsomal triglyceride transfer protein (MTP). In addition, PDI deficiency in hepatocytes abolishes Apolipoprotein B-100 (ApoB-100) very low-density lipoprotein (VLDL) secretion while maintaining partial ApoB-48 VLDL secretion. In summary, we find that the secretion of UFA esters is PDI-MTP indispensable, while SFA esters could be transferred out of liver via ApoB-48 VLDL through a PDI-MTP-independent pathway.